Prognostic factors influencing survival rates in elderly patients with metastatic renal cell carcinoma - D. V. Semenov; R. V. Orlova; V. I. Shirokorad; S. V. Kostritsky; P. V. Kononets (Южно-Российский онкологический журнал)
Purpose of the study. To determine the influence of prognostic factors on survival rates in patients with metastatic renal cell carcinoma (mRCC) aged ≥ 75 years.Materials and methods. A retrospective study included 77 mRCC patients aged ≥ 75 years who received systemic therapy at the Municipal Oncologic Hospital No. 62 in Moscow and the Municipal Oncologic Dispensary in St. Petersburg from 2006 to 2019. Clinical data from medical records were obtained and analyzed retrospectively, all patients underwent clinical, laboratory, and pathomorphological examination. Patients' survival rates were evaluated using the statistical method of survival time analysis (Survival Analysis). Descriptive characteristics of survival time were calculated in the form of life tables, and Kaplan-Meier curves were constructed.Results. In the present study, a favorable prognosis according to International Metastatic Renal Cell Carcinoma Database Consortium (IMDC)was noted in 20.8 % of patients with mRCC aged ≥ 75 years; 6.5 % had solitary metastases. The 3- and 5-year survival rates were 35.8 % and 21.2 %.In single-factor analysis in mRCC patients ≥ 75 years of age, it was found that ECOG status (p < 0.001), histological subtype (p = 0,01), Fuhrman grade of tumour differentiation (p = 0.003), type of metastases (p = 0.045), liver metastases (p < 0.001), IMDC prognosis (p = 0.042) and nephrectomy (p = 0.014).Conclusion. In a multivariate analysis, factors affecting survival in patients with mRCC aged ≥ 75 years included sex, histologic subtype, number of metastases, bone and lymph node metastases, IMDC prognosis, and radiation therapy and nephrectomy. Further studies are needed to identify additional personalized prognostic factors in elderly patients with mRCC.